Biodegradation of polyethylene terephthalate microplastics by Paenibacillus naphthalenovorans PETKKU2: Response surface optimization and genomic evidence for an alternative degradation mechanism - Aophat Choonut; Nantharat Wongfaed; Auraiwan Poolpol; Sophon Boonlue; Kitirote Wantala; Onruthai Pinyakong; Pensri Plangklang; Alissara Reungsang (PLoS ONE, 2026)
This study establishes Paenibacillus naphthalenovorans PETKKU2, isolated from landfill soil in Thailand, as the first reported member of this species capable of degrading polyethylene terephthalate microplastics (PET-MP). Initial screening identified PETKKU2 as the most efficient degrader among ten isolates, achieving 6.07 ± 0.18% weight loss after 35 days at 37°C. Response surface methodology optimization of pH, nitrogen concentration, and PET-MP loading enhanced degradation to 9.48 ± 0.21%, closely matching the predicted maximum of 11.15% and representing 96% improvement over baseline conditions. Integrated analytical characterization (FTIR, SEM, GC-MS) revealed an alternative degradation mechanism distinct from classical PETase-MHETase pathways. FTIR analysis confirmed extensive polymer oxidation with 41% reduction in ester carbonyl groups, while SEM demonstrated progressive surface erosion. Critically, the absence of mono(2-hydroxyethyl) terephthalate (MHET) intermediates, combined with whole-genome analysis revealing thermostable lipases, carboxylesterases, and dioxygenases, but no PETase/MHETase homologs, indicates novel enzymatic routes. Operating under mesophilic conditions (37 °C), PETKKU2 eliminates energy-intensive heating requirements while achieving performance comparable to established thermophilic degraders. These findings establish a promising platform for sustainable PET-MP bioremediation and advance understanding of alternative microbial plastic degradation mechanisms.